Consequences of postnatal stress: maternal separation in rats induces long-lasting changes on glutamate transporters - Odeon, Maria Mercedes (2013)
Background: There is increasing evidence that environmental factors, particularly stressful events experienced early in life, increase the risk of developing a psychiatric illness and/or a behavioural disorder. The aim of this study was to evaluate the effects of acute and chronic maternal separation (AMS and CMS) plus cold stress on the expression patterns of Glutamate Transporters (TGlus) in the developing and young adult Central Nervous System (CNS). As regulation of Glutamate (Glu) extracellular levels is of key importance, sodium-dependent Glu uptake using synaptosome-enriched fractions isolated from Frontal Cortex (FC) and Hippocampus (Hic) was also studied. Results: In animals under AMS stress found that Glu uptake decreases with respect to control groups. Meanwhile in CMS did not observe changes on Glu uptake in adult animals. These data would suggest the existence of an adaptive mechanism that could compensate the effect of AMS and CMS plus cold stress on glutamate uptake. Western blotting was performed in homogenates prepared from FC and Hic from both neonate and young adult rat brains. These blots exposed that homogenates include GLT-1 and EAAC-1 proteins and their levels varied in different areas of the rat brain and with the age of animals. Conclusions: During early postnatal life, exposure to various stressors lead to the development of various neurological, psychiatric, neurodegenerative and behavioral disorders, expressible in adult life in the case of chronic stress. These results demonstrate that adverse early life events have profound and persistent effects on brain function and may represent a risk factor for the development of psychopathology later life.